Neural control meets biomechanics in the motor assessment of neurological disorders: a narrative review - Bonanno, Mirjam; De Pasquale, Paolo; Fonti, Bartolo; Gjonaj, Elvira; De Salvo, Simona; Quartarone, Angelo; Calabrò, Rocco Salvatore (Frontiers in Neural Circuits, 2025)
The emerging concept of “neurobiomechanics” embodies an integrative approach, bringing together insights from functional anatomy, the physiology of the musculoskeletal and central nervous systems, physics, and computer science. By examining human movement under normal, optimal, and pathological conditions, neurobiomechanics aims to unravel the intricate mechanisms driving motor function and dysfunction, offering a comprehensive perspective on disorders such as acquired brain injury and neurodegenerative diseases. In this narrative review, we sought to explore the “neurobiomechanics” as a potential approach to investigate both neural and biomechanical aspects of human motion, trying to answer the following questions: (1) “Which technologies can perform a neurobiomechanical assessment in neurological patients?,” (2) “What are the key neurophysiological and biomechanical parameters?,” (3) “How can we translate this approach from research to clinical practice?.” We have found that, to assess/understand a patient’s dysfunctional patterns, it is necessary to evaluate both neurophysiology and biomechanics in a complementary manner. In other words, assessing one aspect without the other is not sufficient, as this may lead to incomplete evaluations from both a functional and methodological perspective.